Green Perovskite Light‐Emitting Diodes with 200 Hours Stability and 16% Efficiency: Cross‐Linking Strategy and Mechanism. (17th April 2021) - Han, Boning; Yuan, Shichen; Cai, Bo; Song, Jizhong; Liu, Wenqiang; Zhang, Fengjuan; Fang, Tao; Wei, Changting; Zeng, Haibo
Abstract: According to the thinner emitting layer and stronger electric field in perovskite light‐emitting diodes (PeLEDs) than those in perovskite solar cells, the strong electric‐field‐driven ion‐migration is a key issue for the operational stability of PeLEDs. Here, a methylene‐bis‐acrylamide cross‐linking strategy is proposed to both passivate defects and suppress ion‐migration with an emphasis on the suppressing mechanism via in situ investigations. As typical results, in addition to the enhanced external quantum efficiency (EQE, 16.8%), PeLEDs exhibit preferable operational stability with a half lifetime ( T 50 ) of 208 h under continuous operation with an initial luminance of 100 cd m −2 . Moreover, the EQE of cross‐linked LEDs can maintain above 15% during 25 times scanning as the devices are measured every 4 days. To the authors' knowledge, this is the highest stability published until now for high‐efficiency PeLEDs with EQE over 15%. The in situ/ex situ mechanism investigation demonstrates that such cross‐linking increases binding energy from 0.54 to 0.92 eV and activation energy from 0.21 to 0.5 eV. Hence, it suppresses ligands breaking away and ion migration, which prevents ions from moving inside and across crystals. The proposed cross‐linking passivation strategy thus provides an effective methodology to fabricate stable perovskites‐based photoelectric devices. Abstract : High‐efficiency green perovskite light‐emitting diodes (PeLEDs) with high operational stability are obtained via cross‐linking passivation strategy to suppress ion‐migration in halide perovskite. PeLED operational stability is improved to have a T 50 of 208 h and the maximum external quantum efficiency (EQE) of 16.8%, representing the highest stability for high‐efficiency green PeLEDs until now with an EQE over 15%.